2001
DOI: 10.1002/1097-0231(20010215)15:3<182::aid-rcm208>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Ratiometric analysis of the ferrocene boronate esters of 2- and 4-hydroxyestradiol by tandem electrospray mass spectrometry

Abstract: A method has been developed for the semiquantitative analysis of the catechol estrogens, 2‐ and 4‐hydroxyestradiol, using tandem electrospray mass spectrometry in a quadrupole ion trap mass analyzer. The implication of catechol estrogens in the biogenesis of breast and prostate cancer makes these labile lipophilic compounds important analytical targets. Ferrocene boronic acid is reacted with 2‐ and 4‐hydroxyestradiol to form their cyclic boronate esters. Sample ionization is accomplished during the electrospra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 21 publications
(28 reference statements)
1
13
0
Order By: Relevance
“…Distinction between the diastereomers of mono-and disaccharides was achieved. The same arrangement was used for semiquantitative analysis of the derivatized catechol estrogens, 2-and 4-hydroxyestradiol [62]. Collision-induced dissociation of the radical cations produced fragment ion spectra that enabled distinction between the two isobaric isomers.…”
Section: Redox Reactions In the Electrospray Ionization Interfacesupporting
confidence: 78%
“…Distinction between the diastereomers of mono-and disaccharides was achieved. The same arrangement was used for semiquantitative analysis of the derivatized catechol estrogens, 2-and 4-hydroxyestradiol [62]. Collision-induced dissociation of the radical cations produced fragment ion spectra that enabled distinction between the two isobaric isomers.…”
Section: Redox Reactions In the Electrospray Ionization Interfacesupporting
confidence: 78%
“…1 (20 mL) and mixed with 220 mg (2.4 mmol) maleic anhydride, which was also dissolved in dry THF (10 mL). After stirring the reaction mixture for one hour in an ice bath, the solvent was removed by evaporation and the crude N-(2-ferroceneethyl)maleic acid (4) obtained was, in contrast to the approach described in the literature [12], purified by column liquid chromatography using silica gel with ethyl acetate/chloroform (9:1) as the mobile phase. ESI-MS: m/z = 327 [M+H] + .…”
Section: Methodsmentioning
confidence: 99%
“…Ferrocene-based derivatizing agents were used for other classes of compounds too. Semiquantitative analysis of catechol estrogens as their ferrocene boronate esters using ESI-MS with one-electron oxidation in the source using a nonaqueous solvent system (a mixture of dichloromethane and acetonitrile (ACN) with lithium triflate as the working electrolyte) was applied by Williams et al [12]. 1α-Hydroxyvitamin D 3 in rat plasma was determined by ESI-MS after derivatization with 4-ferrocenylmethyl-1,2,4-triazoline-3,5-dione by Murao et al [13].…”
Section: Introductionmentioning
confidence: 99%
“…Due to susceptibility of the boronates to solvolysis, they have generally been used in normal-phase LC. 10 However, Gamoh and co-workers have demonstrated the utility of boronates for characterization of 1,2-diol compounds in reversed-phase LC 11 and LC/MS. 12 We also found that the boronates examined in this study were remarkably stable in the mobile phase using MeCN, though they were solvolyzed in aqueous MeOH.…”
Section: Effect Of Derivatization With Boronic Acid Derivatives For Tmentioning
confidence: 99%